Dimeric- and trimeric sesquiterpenes from the flower of Inula japonica. (November 2018) - Jin, Qinghao; Lee, Jin Woo; Jang, Hari; Lee, Hye Lim; Kim, Jun Gu; Wu, Wanying; Lee, Dongho; Kim, Eun-Hee; Kim, Youngsoo; Hong, Jin Tae; Lee, Mi Kyeong; Hwang, Bang Yeon
Abstract: An undescribed unusual sesquiterpene trimer and three sesquiterpene dimers were isolated from the flowers of Inula japonica . Their structures were elucidated by extensive analysis of 1D and 2D NMR spectroscopic data as well as HRESIMS data. Inulajaponicolide A has an undescribed carbon skeleton comprising of one xanthanolide and two guaianolide units with the linkage mode of C-11/C-3ʹ and C-11ʹ/C-1ʹʹ via a Diels-Alder cycloaddition reaction. Inulajaponicolides C and D exhibited moderate cytotoxic activity against A 549 and NCI-H460 human cancer cell lines with IC50 values ranging from 8.5 to 17.8 μM. Inulajaponicolides A-D and lineariifolianoid A possessed significant inhibitory potency against nitric oxide production in LPS-induced RAW264.7 cells with IC50 values ranging from 1.0 to 4.1 μM. Graphical abstract: An undescribed unusual sesquiterpene trimer and three sesquiterpene dimers were isolated from the flowers of Inula japonica . Some of the isolates were showed cytotoxic and NO inhibitory activities. Highlights: Four sesquiterpenes were isolated from Inula japonica. Inulajaponicolide A is an unprecedented sesquiterpene trimer formed by both endo- and exo-type 1, 3-linked Diels-Alder cycloaddition. Inulajaponicolides B-D are biogenetically related sesquiterpene dimers. Some of the isolates were showed cytotoxic and NO inhibitory activities.